Endovascular intervention robot with multi-manipulators for surgical procedures: Dexterity, adaptability, and practicability. (April 2019) - Wang, Kundong; Lu, Qingsheng; Chen, Bin; Shen, Yu; Li, Hongbing; Liu, Manhua; Xu, Zhuoyan
Highlights: This robot used four manipulators with high dexterity to imitate the four hands of main surgeon and his assistant for intervention procedures. The self-adapted gripper is compatible with the most conventional devices, especially to the stent deploying handles. There are total 12 DOFs to realize the complex surgical actions such clamping, push-pull, and rotation of the single guide wire, catheter or other devices. A complete endovascular intervention procedure with successful deploying of three stents and zero radiation damage to the surgeon was demonstrated. Abstract: In this research, a novel vascular intervention robot with four manipulators that mimic the four hands of a physician and an assistant was designed for peripheral vessels. Each manipulator has three DOFs (degrees of freedom), namely, clamping, rotation, and push–pull of a guide wire and catheters. Manipulation is accomplished by four corresponding joysticks. A distributed control system is used to coordinate complex motions with high accuracy in real time. This robot can not only manipulate intervention devices but also deploy stents. We performed in-vitro experiments to verify the precise velocity and driving force. A complete endovascular intervention procedure in an in-vivo pig with the successful deployment of three stents and zero radiation damage to the surgeon validated the design. Results showed that the robot had high dexterity, precision, and efficiency, thereby meeting the demands of endovascular intervention surgical procedures.